Red blood cell distribution width to predict mortality in heart transplant recipients: a systematic review - Luis Miguel Acuña-Chávez; Claudia Cruzalegui-Bazán; Carlos Quispe-Vicuña; Clara Saldarriaga; Johanna Contreras; José A. Chávez-Peche; Mayita Alvarez-Vargas; Pedro Segura-Saldaña (Monaldi Archives for Chest Disease, 2022)
Red blood cell distribution width (RDW) has been shown to have prognostic value in a number of different clinical settings, such as cardiovascular disease, including heart failure. However, its prognostic value in heart transplant (HT) recipients remains unknown. The aim of this systematic review is to determine the prognostic value of pre-transplant RDW for mortality in HT recipients. There is a pre-published protocol of this review. The terms "Heart transplant", "Red cell distribution width" and their synonyms were used in the search strategy. PubMed/Medline, Embase, Scopus, Web of Science and LILACS were searched until May 17th, 2022, without date or language restrictions. Two authors independently carried out the selection, first by title and abstract, second by full-text revision. Discrepancies were discussed and resolved with three other authors. Quality of individual studies was assessed with Newcastle Ottawa Scale (NOS) for cohorts. After removing the duplicates, 3885 articles were identified. Four articles were included in the qualitative synthesis. Three studies were classified as “good quality”: whereas one as “poor quality” according to NOS scale. All the included articles evaluated long-term mortality and one study also evaluated short-term mortality. In this one, a correlation between higher RDW values and short-term mortality was reported. Meanwhile, in all the studies, a high pre-HT RDW was a marker of long-term mortality following cardiac transplantation. Our review shows that an elevated on-admission RDW is associated with long-term mortality in heart transplantation recipients.